Selecting Soil Salinity Layer that Better Correlates with Sugarcane Recoverable Sugar Yield - Valdivia Vega, Sergio; Pinna Cabrejos, Jorge; Valdivia Salazar, Sergio (Agrociencia Uruguay, 2016)
The objective of this work was to find out which soil salinity layer correlated better with the recoverable sugar yield. The present study was made at Zapote field, located at Tumán enterprise, in Peruvian northern coast, Lambayeque Department, Peru. The soil (salinity 2 to 8 dS m-1 ) was planted with sugarcane (Saccharum spp.) H32-8560 cultivar on 105 plots harvested at five different ages, fertilized with 5 N doses and a control without fertilization. Lineal correlations between sugar yield and salinity, expressed as Electrical Conductivity of saturation extract (CEe), of different soil layers (0-30 cm, 30-60, 60-90, mean 0-60, mean 0-90, higher salty layer 0-60, and less salty layer 0-60 cm) were calculated. Moreover, sugar yield was correlated with ten arithmetical and pondered means of salinity measured before planting and after harvesting. Higher correlation was found for salinity measures before planting than with measures after harvesting. The highest correlations with sugar yields utilizing salinity measures before planting, corresponded with mean 0-60 cm salinity layer, with R values between 0.27 and 0.84 (p<0.01), the less salty layer 0-60 cm, with R between 0.47 (p<0.01) and 0.82 (p<0.01), and the most salty layer 0-60 cm with values from 0.04 to 0.81 (p<0.01). Conclusion: it is enough sampling and analyzing soils just to 60 cm before planting.